2022
DOI: 10.3390/agriculture13010073
|View full text |Cite
|
Sign up to set email alerts
|

Applying Silver Nanoparticles to Enhance Metabolite Accumulation and Biodiesel Production in New Algal Resources

Abstract: Biofuel generation from algae can be increased by using nanotechnology. The present study emphasizes the use of silver nanoparticles on algae for algal fuel generation along with the impact of nanoparticles on biomass, metabolites and lipid profile. Silver ion amassing was enhanced in each algal species, but maximum phytoremediation was found in Ulothrix sp. Carbohydrates increased 3.2 times in Oedogonium sp., 3.3 times in Ulothrix sp., 3 times in Cladophora sp. and 2.7 times in Spirogyra sp. Additionally, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Thus, stimulatory effects of some nanoparticles on lipid accumulation have been revealed in other algal cultures treated with different types of nanoparticles: Oedogonium sp., Cladophora sp., Ulothrix sp., and Spirogyra sp. using AgNPs ( Hasnain et al, 2023 ); Scenedesmus obliquus exposed to Fe 2 O 3 and Fe 3 O 4 nanoparticles ( He et al, 2017 ; Wang et al, 2021 ); Trachydiscus minutus , Desmodesmus subspicatus and zerovalent iron (ZVI) nanoparticles ( Pádrová et al, 2015 ); Chlorella vulgaris upon influence of TiO 2 nanoparticles and MgNPs ( Kang et al, 2014 ; Sibi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, stimulatory effects of some nanoparticles on lipid accumulation have been revealed in other algal cultures treated with different types of nanoparticles: Oedogonium sp., Cladophora sp., Ulothrix sp., and Spirogyra sp. using AgNPs ( Hasnain et al, 2023 ); Scenedesmus obliquus exposed to Fe 2 O 3 and Fe 3 O 4 nanoparticles ( He et al, 2017 ; Wang et al, 2021 ); Trachydiscus minutus , Desmodesmus subspicatus and zerovalent iron (ZVI) nanoparticles ( Pádrová et al, 2015 ); Chlorella vulgaris upon influence of TiO 2 nanoparticles and MgNPs ( Kang et al, 2014 ; Sibi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mar. Drugs 2024, 22, x 2 of 15 microalgae for biofuel production purposes [10][11][12]. However, this effect is more often a result of the stress caused by high concentrations of these nanoparticles.…”
Section: Quantity Of P Purpureum Cnmn-ar-02 Biomass Produced Under Cu...mentioning
confidence: 99%
“…In the context of applying stimulants to produce higher amounts of biomass with a valuable and predictable biochemical content, nanoparticles of various natures are increasingly being explored from this perspective [8,9]. For example, nanoparticles of Mg, Al, Zn, Cu, Pb, Ag, Fe, Fe 3 O 4 are used as effective stimulants to enhance lipid synthesis in microalgae for biofuel production purposes [10][11][12]. However, this effect is more often Mar.…”
Section: Introductionmentioning
confidence: 99%
“…Rana et al [80] reported that using Fe 2 O 3 nanoparticles increased the growth and lipids of Chlorella pyrenoidosa by 33.75% and 15.2%, respectively. Recently, Hasnain et al [81] recorded that lipid content highly significantly accumulated in Oedogonium sp., Ulothrix sp., Cladophora sp., and Spirogyra sp. by 60%, 56%, 58%, and 63%, respectively when exposed to AgNPs.…”
Section: Physiological Responses Of C Chodatii To Different Levels Of...mentioning
confidence: 99%